ANALISIS STABILITAS TIMBUNAN (MAINDAM) BERDASARKAN DATA INSTRUMEN GEOTEKNIK PADA BENDUNGAN SINDANG HEULA SERANG BANTEN - Nanang Sutisna; M. Ichwanul Yusup; Euis Amilia Euis Amilia (Journal of Sustainable Civil Engineering (JOSCE), 2021)
The development of science and technology has obtained supporting technology for monitoring the soil shear force and pore water pressure in the dam, the presence of shear forces against the landfill and pore water pressure through small cavities in the embankment soil in the dam body which can be detected by equipment such as inclinometer and piezometer that have been installed at predetermined points. The application of inclinometer and piezometer technology is used as a support tool for monitoring the movement of landfill and pore water pressure against dams. The embankment dam is the most complex of civilian structures and is very dangerous if damaged. When there is damage to a dam, it will cause a big disaster for the areas that are downstream of the dam. Damage or collapse of a dam can occur due to several things, including overtopping, sliding of the dam slopes (internal erosion or "piping"), and the occurrence of structural degradation of each zone. on the dam body. In the analysis of the stability of the embankment (maindam) which is based on geotechnical instrument data, it must be carried out as carefully and accurately as possible. The purpose of this analysis is to measure the early damage in the main dam (maindam). After conducting research and field studies at the Sindang Heula dam, there were several points of decline at the top of the core embankment (maindam). To find out the cause of the decline, data was taken from measuring geotechnical instruments.